Educational Process Organization in Higher Education: Technology and Innovation for Sustainable Development - Derstuganova, Natalia; Hubina, Oksana; Zheinova, Svitlana; Imanberdiev, Dosaaly; Ostrohliad, Andrii (European Journal of Sustainable Development, 2025)
Modern higher education system should be proactive in incorporating new innovative technologies to meet modern societal needs and improve the quality of learning in general. In the university, new digital solutions are now more focused on transformation processes and competency-based education. This article aims at examining the extent to which such technologies can be integrated within the organization of educational activities at higher institutions of learning. The study design involved surveys, data analysis and statistical analysis of the data gathered. On the basis of these results, the authors suggested a framework of the introduction of innovative technologies at different levels of study. At the undergraduate level, the emphasis is put on digital learning platforms, virtual laboratories, simulations and interactive tools. Master programs also focus on learning analytics, incorporation of education resources, and project-based practices. In the case of doctoral training, cloud-based services and virtual research laboratories are central. In order to quantify the results, certain measures of technological use in the learning process were created and their usefulness was statistically confirmed. The adaptive strategies of learning, digital resources, and the implementation of augmented and virtual reality can support the development of critical thinking, learning personalization, and communication and research skills in graduate and postgraduate students. Keywords: future educators, pedagogical activity, general competencies, doctors of philosophy, innovative technologies, organization of the educational process, higher education institutions, sustainable innovations.